2022
DOI: 10.1108/ijchm-12-2021-1554
|View full text |Cite
|
Sign up to set email alerts
|

The transformative virtual experience paradigm: the case of Airbnb’s online experience

Abstract: Purpose This research paper aims to explore Airbnb’s online experience initiative, which has sparked a new wave of virtual tourism to improvise a large assortment of experiential activities through cyberspace. It works to answer questions pertinent to the type of virtual experiences tourists seek and how these experiences could fulfill tourist needs, thereby rendering favorable socio-mental outcomes through experiences encountered. Design/methodology/approach Drawing on travel experience and transformative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Some researchers have deemed it as superficial (Zuev and Picard, 2015) and lack coverage of the theory in the findings, or it is conceptualized in a way that lacks empirics (Joo et al , 2020; Bargeman and Richards, 2020). Special events and other hospitality services, however, entail transformative potential to change peoples’ status quo (Soulard et al , 2021; Sterchele, 2020) and the ability to awaken their consciousness to a social agenda (Sheldon, 2020; Wong et al , 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have deemed it as superficial (Zuev and Picard, 2015) and lack coverage of the theory in the findings, or it is conceptualized in a way that lacks empirics (Joo et al , 2020; Bargeman and Richards, 2020). Special events and other hospitality services, however, entail transformative potential to change peoples’ status quo (Soulard et al , 2021; Sterchele, 2020) and the ability to awaken their consciousness to a social agenda (Sheldon, 2020; Wong et al , 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…emotional energy, group solidarity, symbols of relationship and standards of morality). This research also adds to the transformative service literature by extending the transformative role of hospitality (Galeone and Sebastiani, 2021; Wong et al , 2023) to the self–community–society paradigm, which anchors on the micro–macro linkage among these social echelons. It, thus, sheds new light on the event literature by taking a leap forward in understanding the transformative role of special events (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wong et al (2023) examined Airbnb’s online experience initiative, which offers virtual tourism activities. The authors adopted transformative tourism theory and identified four major themes in online experiences – hedonism, attention restoration, social relatedness and self-exaltation.…”
Section: Guest Editorial For Ijchm Vol 35 Issue 4 2023 On Sharing Eco...mentioning
confidence: 99%
“…Their qualitative analysis of 24 restaurant managers and 29 customers underscores the importance of optimizing digitalization of services to enhance the uniqueness of the dining experience for an enhanced customer journey. Wong et al (2023a) studied Airbnb's online experience initiative of virtual tourism by considering the nature of virtual experiences sought by tourists and how their needs are met. Their study reported four themes to be of importance: hedonism, attention restoration, social relatedness and self-exaltation which are linked to well-being.…”
Section: Ijchm 367mentioning
confidence: 99%